A Novel Three‐Phase Interface Premelting Theory for Determining Unfrozen Water Content in Unsaturated Soil - Xusheng Wan; Jishuai Zhu; Wansheng Pei; Weibo Liu; Fengxi Zhou (Water Resources Research, 2025)
Abstract The soil above the water table in the shallow layers of the Earth is typically unsaturated, and understanding the complicated multiphase contact modes and interactions in unsaturated is crucial for accurately simulating multi‐physical field coupling and predicting foundation deformation in frozen soil region. In this study, a theoretical model for unfrozen water content in unsaturated soils by integrating the generalized interface premelting theory with Gibbs free energy minimization. The model resolves the phase transition processes at the interfaces of air‐water‐ice‐soil by determining air‐phase distribution within pore spaces and incorporating interfacial melting effects at air‐ice and soil‐ice boundaries. Additionally, we incorporated the concept of effective water content to improve calculation accuracy, and the model was validated using experimental data. The results indicate that the equilibrium contact angle between air and soil particles is primarily influenced by air saturation and is independent of soil pore size. As air saturation increases, the equilibrium contact angle and the radius of the ice‐water curvature interface enlarges, the melting effect between soil particles and ice crystals diminishes, and the unfrozen water content decreases. In addition, soils with smaller pore sizes and lower saturation exhibit higher surface free energy, which inhibits ice nucleation. Consequently, the soil freezing characteristic curve (SFCC) of silty clay demonstrates significant sensitivity to air saturation, unlike coarse‐grained soils (e.g., silt, sand), where air saturation minimally influences the SFCC. These results advance predictive frameworks for hydrothermal behavior in unsaturated frozen soils, particularly in fine‐grained geomaterials.